Research progress of scales for assessment of post-stroke depression (脑卒中后抑郁评估量表的研究进展) - CHEN Shanshan (陈闪闪); GUO Hong (郭红); GONG Shaohua (弓少华); HU Nannan (胡楠楠); ZHANG Ao (张傲) (中西医结合护理)
Post-stroke depression is one of the most common compilations affecting the rehabilitation of patients after stroke. It is required to assess the severity of post-stroke depression. There are two main scales for assessment of post-stroke depression: self-rating scales and examiner-rating scales. The clinical works and researcher should choose the suitable scale in different situations and ensure the accuracy of assessment outcomes. This paper reviewed the self-rating and examiner-rating scales for assessment of post-stroke depression, in order to provide reference for rational selection of scales for assessment of post-stroke depression. (卒中后抑郁作为脑卒中最常见的并发症之一, 严重影响着脑卒中患者的康复。及时评估诊断卒中后抑郁对于尽早治疗具有重要的意义。目前对于卒中后抑郁测量评估的量表主要有自评和他评两类, 临床工作者和科研工作者在不同的情景下选用合适的量表, 对确保测量评估结果的准确性具有重要的意义。本文主要综述了目前研究中常用于测量评估卒中后抑郁患者的自评及他评量表, 以期为研究者选择合适的卒中后抑郁评估工具提供借鉴和参考。)